2017
DOI: 10.1080/24740527.2017.1399053
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on the study of siblings in pediatric pain

Abstract: Background: Sibling relationships are longstanding across an individual's life and are influential in children's development. The study of siblings in pediatric pain is, although in early stages, a growing field. Aims: This scoping review sought to summarize and map the type of research available examining siblings and pediatric pain to identify gaps and directions for future research. Methods: Studies were identified based on a search of PubMed, CINAHL, PsycInfo, Embase, and Web of Science (up to November 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…Additionally, there was a lack of highpowered quantitative papers in this area. Overall, these suggestions for future research build on recommendations from previous reviews which identified a need for more research to adopt a developmental perspective and longitudinal approach (Palermo et al, 2014), and exploring familial influences in the development of young people with chronic pain (Schinkel et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, there was a lack of highpowered quantitative papers in this area. Overall, these suggestions for future research build on recommendations from previous reviews which identified a need for more research to adopt a developmental perspective and longitudinal approach (Palermo et al, 2014), and exploring familial influences in the development of young people with chronic pain (Schinkel et al, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, there is no published literature on this topic. 34 However, research in other areas of mental health has shown that sibling bullying victims initially assessed at 12 years of age have increased odds of depression, suicidal ideation, and self-harm behaviors in early adulthood at the age of 24 years. 35 Moreover, youth bullied by both siblings and peers showed even higher odds of negative mental health outcomes.…”
Section: Future Researchmentioning
confidence: 99%
“…And finally, pediatric pain research has only recently begun to explore the role of the sibling in childhood adjustment to pain. 90 , 91 Much of the work to date has focused on the genetic influence or vulnerability of the sibling, rather than exploring sibling influences and experiences from a family systems perspective. Of particular relevance to the present discussion is the degree to which the CPSP trajectory is influenced by the presence of a sibling(s).…”
Section: Future Researchmentioning
confidence: 99%